PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT ANDAL SOFTWARE SEJAHTERA JAKARTA PUSAT - Dwi Maryani, Firda; Sulistiani, Sinta (Journal of Research and Publication Innovation, 2024)
performance at PT Reliable Software Sejahtera Central Jakarta. The method used is a quantitative approach The number of population and samples is 50 with a saturated sampling technique. The analysis method uses validity test, reliability test, classical assumption test, Descriptive Analysis, Quantitative Analysis, and Hypothesis Test. Work discipline has a positive and significant effect on employee performance with the regression equation X1 Y 10.364 + 0.771 X1, the correlation coefficient value is obtained at 0.888, meaning that the two variables have a very strong relationship level. The value of determination or contribution of influence is 78.9% while the remaining 21.1% is influenced by other factors. The hypothesis test obtained a value of t calculated > t table or (13,400 > 2,010) thus H01 was rejected and Ha1 was accepted. The physical work environment has a positive and significant effect on employee performance with the regression equation X2 Y 12.497 + 0.706X2, the correlation coefficient value is obtained at 0.877, meaning that the two variables have a very strong relationship. The value of determination or contribution of its influence is 76.9% while the remaining 23.1% is influenced by other factors. The hypothesis test obtained a t-value calculated > t table or (12.637 > 2,010). Thus H02 is rejected and Ha2 is accepted. Work discipline and physical work environment simultaneously have a positive and significant effect on employee performance with the regression equation Y 9.183 + 0.771 X1 + 0.706 X2. The value of the determination coefficient or contribution of its influence simultaneously was 83.7% while the remaining 16.3% was influenced by other factors. The hypothesis test was obtained with an F value calculated > F table or (120,961 > 2,802). Thus H03 is rejected and Ha3 is accepted.